When students from different professions are co-located: the importance of interprofessional rapport for learning to work together. Issue 1 (January 2015) - Croker, Anne; Fisher, Karin; Smith, Tony
Abstract With increasing interest and research into interprofessional learning, there is scope to more deeply understand what happens when students from different professions live and study in the same location. This study aimed to explore the issue of co-location and its effects on how students learn to work with other professions. The setting for this study was a rural health education facility in Australia with close links to local health care and community services. Philosophical hermeneutics informed the research method. Interviews were undertaken with 29 participants, including students, academic educators and clinical supervisors in diagnostic radiography, medicine, nursing, nutrition and dietetics, pharmacy, physiotherapy, occupational therapy, and speech pathology. Photo-elicitation was used to facilitate participant engagement with the topic. The findings foreground the value of interprofessional rapport building opportunities for students learning to work together. Enabled by the proximity of different professions in shared educational, clinical and social spaces, interprofessional rapport building was contingent on contextual conditions (balance of professions, shared spaces and adequate time) and individual's interpersonal capabilities (being interested, being inclusive, developing interpersonal bonds, giving and receiving respect, bringing a sense of own profession and being patient-centred). In the absence of these conditions and capabilities, negative professional stereotypes may be inadvertently re-enforced. From these findings suggestions are made for nurturing interprofessional rapport building opportunities to enable students of different professions to learn to work together.